Age at introduction of ultra-processed food among preschool children attending day-care centers, - Giovana Longo-Silva; Jonas Augusto C. Silveira; Rísia Cristina Egito de Menezes; Maysa Helena de Aguiar Toloni
Abstract Objective: To identify the age of introduction of ultra-processed food and its associated factors among preschool children. Methods: Cross-sectional study carried out from March to June 2014 with 359 preschool children aged 17 to 63 months attending day-care centers. Time until ultra-processed food introduction (outcome variable) was described by the Kaplan-Meier analysis, and the log-rank test was used to compare the survival functions of independent variables. Factors associated with ultra-processed food introduction were investigated using the multivariate Cox proportional hazards model. The results were shown as hazard ratios with their respective 95% confidence intervals. Results: The median time until ultra-processed food introduction was six months. Between the 3rd and 6th months, there is a significant increase in the probability of introducing ultra-processed food in the children's diet; and while the probability in the 3rd month varies from 0.15 to 0.25, at six months the variation ranges from 0.6 to 1.0. The final Cox proportional hazards model showed that unplanned pregnancy (1.32 [1.05-1.65]), absence of prenatal care (2.50 [1.02-6.16]), and income >2 minimum wages (1, 50 [1.09-2.06]) were independent risk factors for the introduction of ultra-processed food. Conclusion: Up to the 6th month of life, approximately 75% of preschool children had received one or more ultra-processed food in their diet. In addition, it was observed that the poorest families, as well as unfavorable prenatal factors, were associated with early introduction of ultra-processed food.